Oral and nasal microbiota in Parkinson's disease. (May 2017) - Pereira, Pedro A.B.; Aho, Velma T.E.; Paulin, Lars; Pekkonen, Eero; Auvinen, Petri; Scheperjans, Filip
Abstract: Introduction: Parkinson's disease (PD) is associated with neuropathological changes in olfactory and gastrointestinal tissues, and PD patients frequently suffer from hyposmia, hyposalivation, and dysphagia. Since hyposmia and gastrointestinal dysfunction are frequently premotor symptoms, it has been speculated that an external, for example microbial, agent could trigger the pathologic process in the corresponding organs, subsequently spreading to the central nervous system. We recently showed evidence for compositional differences between the fecal microbiota of PD patients and control subjects. In this study, our objective was to explore a possible connection between nasal and oral microbiota and PD. Methods: We compared the oral and nasal bacterial communities of PD patients (oral: n = 72, nasal: n = 69) and control subjects (oral: n = 76, nasal: n = 67) using a 16S rRNA gene amplicon sequencing approach. Results: Oral and nasal microbiota differed markedly from each other, with no notable similarity within subjects. Oral microbiota of PD patients and control subjects had differences in beta diversity and abundances of individual bacterial taxa. An increase in the abundance of opportunistic oral pathogens was detected in males, both with and without PD. Our data did not reveal convincing differences between the nasal microbiota of control subjects and PD patients. Conclusion: The oral microbiome deserves additional research regarding its connection to PD and its biomarker potential. The higher abundance of oral pathogens in men underlines the importance of monitoring and promoting male dental health. Highlights: Oral microbiota differed between PD patients and control subjects. Opportunistic oral pathogens were increased in male subjects. No convincing differences of nasal microbiota were found. Oral microbiota deserve further exploration as a potential PD biomarker.